2018
DOI: 10.24193/subbchem.2018.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater Quality and Associated Health Risks in Rural Areas of Sindh (Pakistan)

Abstract: ABSTRACT. Groundwater quality has considerable impact on public health, especially in areas where majority of the people rely on groundwater for drinking purpose. In this scenario, investigation of 175 groundwater samples collected from district Jacobabad and Kashmor, Sindh Pakistan was carried out for physicochemical parameters (color, odor, taste, pH, EC, turbidity, alkalinity, hardness, Cl, SO 4 -2 , NO 3 -and TDS), major cations (Naand Mg +2 ), trace elements (F, As, Fe and Zn) and microbiological organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…South Sindh mainly depends on surface water for drinking water, and that water appears to be highly contaminated with E. coli (Umerkot 68.9%, Karachi 60%, and Sujawal 57.5%). The high risks of infections that we found in the present study are congruent with other available studies of drinking water in Pakistan [15,24,35]. The latest Pakistan demographic and health survey in the community settings of the study area reported a high prevalence of waterborne diseases, such as diarrhea, dysentery, cholera, and typhoid [36], which aligns with the high-risk pathogens we found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…South Sindh mainly depends on surface water for drinking water, and that water appears to be highly contaminated with E. coli (Umerkot 68.9%, Karachi 60%, and Sujawal 57.5%). The high risks of infections that we found in the present study are congruent with other available studies of drinking water in Pakistan [15,24,35]. The latest Pakistan demographic and health survey in the community settings of the study area reported a high prevalence of waterborne diseases, such as diarrhea, dysentery, cholera, and typhoid [36], which aligns with the high-risk pathogens we found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…A large number of other investigations have also been carried out to evaluate physicochemical and microbiological quality of drinking water and possible health risks. Most of water samples analyzed in these studies were found unfit for human consumption on grounds of either chemical and/or microbiological contamination (Oyem, Oyem, & Usese, 2015;Alamgir, Khan, Schilling, Shaukat, & Shahab, 2016;Mohsin, Safdar, Asghar, & Jamal, 2013;Sarfraz, Sultana, Jamil, & Ashraf, 2016;Sarfraz, Sultana, & Jamil, 2018a;Sarfraz, Sultana, & Tariq, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Its quality changes throughout time and space. It varies depending on the depth of the water table and the location (Sarfraz, et al, 2018). Reid according to estimates, 75% of people in affluent countries lack access to clean water to drink, among many other issues.…”
Section: Introductionmentioning
confidence: 99%